Evaluasi Electronic Government Dalam Meningkatkan Kinerja Pelayanan Publik - Shofy Yorinda Febiyanti; Arimurti Kriswibowo (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
The implementation of online customer complaint handling at PDAM Surya Sembada Kota Surabaya is still not optimal and needs attention considering the importance of public services and PDAM is the only company engaged in the supply of clean water. This study aims to evaluate the implementation of e-government in PDAM Surya Sembada Kota Surabaya in terms of public services. The e-government management of PDAM Surya Sembada Kota Surabaya still has inaccuracies in handling online services, infrastructure indicators found that there is overlapping complaint data entering the system, and the application still does not have a customer service monitoring feature and the application is only available on Android. on Standard Operasional Prosedure (SOP) policy indicators it is necessary to carry out restandardization which is oriented towards e- government innovation. In terms of infrastructure indicators, it is necessary to evaluate the use of the company's internal system. In addition to application indicators, there is a need for innovation to add monitoring features for customers.